2010
DOI: 10.1158/0008-5472.can-09-2942
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia Induces Trimethylated H3 Lysine 4 by Inhibition of JARID1A Demethylase

Abstract: Histone H3 lysine 4 (H3K4) trimethylation (H3K4me3) at the promoter region of genes has been linked to transcriptional activation. In the present study, we found that hypoxia (1% oxygen) increased H3K4me3 in both normal human bronchial epithelial Beas-2B cells and human lung carcinoma A549 cells. The increase of H3K4me3 from hypoxia was likely caused by the inhibition of H3K4 demethylating activity, as hypoxia still increased H3K4me3 in methionine-deficient medium. Furthermore, an in vitro histone demethylatio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
120
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 122 publications
(125 citation statements)
references
References 36 publications
5
120
0
Order By: Relevance
“…S-Adenosylmethionine, which is synthesized from methionine and ATP, is the sole methyl donor for methyltransferase reactions. Histone methylation changes detected in cells grown in media depleted of methionine will predominantly reflect alterations in demethylation as opposed to methylation (33,34,36,37). Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…S-Adenosylmethionine, which is synthesized from methionine and ATP, is the sole methyl donor for methyltransferase reactions. Histone methylation changes detected in cells grown in media depleted of methionine will predominantly reflect alterations in demethylation as opposed to methylation (33,34,36,37). Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Previously, it has been shown that the JMJC domain-containing histone demethylase KDM3A is highly sensitive to inhibition by carcinogenic nickel ions (28,30,31). Others have demonstrated that various dioxygenase inhibitors such as ␣-KG analogs, hypoxia, ⅐ NO, reactive oxygen species, CoCl 2 , and iron chelators like desferrioxamine (DFO) all increase histone methylation, most probably by reducing demethylase activity (32)(33)(34)(35)(36)(37).…”
mentioning
confidence: 99%
“…In contrast, hypoxia increases global levels of H3K4me3 in alveolar A549 and bronchial Beas-2B cell lines, due to the inhibition of demethylation process, particularly, demethylase (Lysinespecific demethylase 5A). Therefore, hypoxia targets lysinespecific demethylase 5A, which induces H3K4me3 both globally and at gene-specific promoters (heme oxygenase-1 and decay-accelerating factor), thus promoting alterations in the pattern of gene expression and tumor progression (194). Understanding the molecular epigenetic mechanism that involves HDMs in COPD/lung cancer will influence treatment options and outcomes in COPD, lung cancer, and other chronic lung diseases associated with tobacco smoking (139).…”
Section: Histone Demethylasesmentioning
confidence: 99%
“…Domains selected for analysis include fragments responsible for DNA interactions; specifically, the β-hairpin which, in the case of PHD domains, is characterized by the stabilizing presence of zinc (Zn 2+ ) ions. Our selection is motivated by the fact that these domains participate in epigenetic phenomena (histone demethylase activity) [18] as well as in polycomb complexation [19][20][21], both of which are important in the context of pathological (disease-related) processes [22,23].…”
Section: Introductionmentioning
confidence: 99%